Pilot‐scale microalgae harvesting with ceramic microfiltration modules: evaluating the effect of operational parameters and membrane configuration on filtration performance and membrane fouling. Issue 3 (30th September 2020) - Bamba, Bio SB; Lozano, Paul; Ouattara, Allassane; Elcik, Harun
Abstract: BACKGROUND: Membrane fouling is one of the major drawbacks in microalgae harvesting that prevents the widespread application of membrane filtration. This study investigates the effects of operating parameters on the filtration performance and the fouling phenomenon of a pilot‐scale microfiltration (MF) system equipped with different ceramic membranes for Chlorella vulgaris culture harvesting. RESULTS: A higher permeate flux was obtained with increasing the transmembrane pressure, resulting in lower irreversible and reversible filtration resistances. On the other hand, at a higher crossflow velocity above 4 m s −1, a high amount of extracellular organic matter (EOM) released by microalgal cells led to a higher irreversible resistance which, in turn, caused severe membrane fouling and a lower filtration flux. Furthermore, the membrane configuration and pore size have also significantly affected the permeate flux. Compared to the tubular membranes, and regardless of pore sizes, the multichannel MF membrane (pore size: 0.2 μm) exhibited a higher permeate flux that resulted in lower membrane resistances due to the lower release of EOM by microalgae cells. Moreover, the tubular membrane (pore size: 0.8 μm) showed a higher flux reduction with higher pore size because of the increase in the irreversible resistance with a high amount of EOM release. CONCLUSION: The results revealed that the amount of EOM significantly associated with filtration conditions plays an important role in membrane fouling control. Considering the membrane configurations, the multichannel ceramic MF membrane (pore size: 0.2 μm) demonstrated a higher permeate flux due to its lower fouling property. © 2020 Society of Chemical Industry (SCI)